Five decades of occupational cancer epidemiology - Michelle C Turner; Kurt Straif; Manolis Kogevinas; Mary K Schubauer-Berigan (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: In this discussion paper, we provide a narrative review of past and present occupational cancer studies in the journal with a viewpoint towards future occupational cancer research. METHOD: We reviewed all references in the journal that mentioned cancer according to relevance to etiology, cancer type, agent type, study design, and study population. RESULTS: The Scandinavian Journal of Work, Environment & Health has published over 300 manuscripts on occupational cancer over the 50 past years. Although studies of cancer represent the primary health outcome in the journal overall, the relative ranking of cancer manuscripts has declined somewhat over time. A large body of evidence from studies of occupation and industry was apparent both in early research and continuing in recent years. There are several examples of the utility of pooled multi-country collaborative studies. Studies also took advantage of available high-quality national population and cancer registers in Nordic countries. There have been notable shifts in focus with regard to the cancer types examined, with increases in publications examining female breast cancer over the decades. The interplay of studies of occupational and environmental cancer has also been apparent. CONCLUSIONS: The journal offers a unique viewpoint to consider the evolution of occupational cancer evidence over time. Studies of occupational cancer have played a central role in global cancer hazard identification efforts. Although much has been gained, there remains a need for renewed global support for occupational cancer research. Concerted efforts will be needed to ensure a future robust evidence-base for occupational and environmental cancer worldwide.